1986
DOI: 10.1083/jcb.103.6.2353
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-secretion coupling in the developing exocrine pancreas: secretory responsiveness to cholecystokinin.

Abstract: Abstract. We have studied the onset of secretory responsiveness to cholecystokinin (CCK) during development of the rat exocrine pancreas. Although acinar cells of the fetal pancreas (1 d before birth) are filled with zymogen granules containing the secretory protein, a-amylase, the rate of amylase secretion from pancreatic lobutes incubated in vitro was not increased in response to CCK. In contrast, the rate of CCKstimulated amylase discharge from the neonatal pancreas (1 d after birth) was increased four-to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 57 publications
2
11
1
Order By: Relevance
“…In contrast to our present results, two proteins of 210 kDa and 100-160 kDa were previously identified as CCK receptors in both foetal and neonatal rat pancreas [7], where affinity labelling of the CCKA receptors was carried out with '251-BH-CCK-33, shown to cross-link not only the receptor but also a neighbouring protein [35]. The present molecular characterization used the cleavable photoactivable CCK ligand, '251-ASD-[Thr34,Ahx37]CCK(31 -39), well characterized as a powerful and specific probe for the pancreatic CCK receptor [17].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast to our present results, two proteins of 210 kDa and 100-160 kDa were previously identified as CCK receptors in both foetal and neonatal rat pancreas [7], where affinity labelling of the CCKA receptors was carried out with '251-BH-CCK-33, shown to cross-link not only the receptor but also a neighbouring protein [35]. The present molecular characterization used the cleavable photoactivable CCK ligand, '251-ASD-[Thr34,Ahx37]CCK(31 -39), well characterized as a powerful and specific probe for the pancreatic CCK receptor [17].…”
Section: Discussioncontrasting
confidence: 56%
“…Additionally, no specific gastrin binding was demonstrated in pancreata of foetal rats (day 19 of gestation). In control adult rats, only by using very high amounts of membrane material and high ligand concentrations were specific '251-BH-de~-S03H-ga~trin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) …”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we show here that dexamethasone induction of a regulated secretory pathway goes hand in hand with an obvious increase in unmethylated rab3D. This phenomenon is strikingly similar to that of the developmental change in rab3D methylation state which occurs during the perinatal period of pancreas development (12), and which also correlates with the acquisition of secretion-stimulus coupling (27). Although these data argue strongly for a role of carboxylmethylation of rab3D in stimulus-secretion coupling, the precise function of carboxyl-methylation is unknown.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have suggested that the unresponsiveness of the term fetal rat pancreas to secretagogue stimulation was related to the low binding capacity of the receptors, whereas the underlying machinery of the stimulus-secretion coupling was already mature (24,25). However, it was suggested in a recent report (26), that the fetal and the neonatal rat pancreas had the same binding capacity to CCK-8. The difference in responsiveness to CCK-8, in terms of amylase release, was viewed as related to an immaturity of the signal transduction events distal to calcium mobilization.…”
Section: Discussionmentioning
confidence: 70%